Characteristics of the first cases reported as suspected Monkeypox in Peru - Pampa-Espinoza, Luis (2022)
The case of 9 patients reported in the context of the health alert due to the increase in cases of Monkeypox virus infection in the world in non-endemic countries is presented. It is important to know in a practical way the most important epidemiological and clinical criteria that make us think about ruling out Monkeypox in the current context of transmission in Peru. The characteristics of the confirmed cases are discussed versus those of other diseases that are part of the differential diagnosis such as chickenpox, hand-foot-mouth syndrome, etc.